(untitled) - Monk, Nicholas (New York, 2011)
"Blood Meridian" and Classical Greek Thought / David Williams -- The Ties that Bind: Intertextual Links between "All the Pretty Horses" and "Sir Gawain and the Green Knight" / Megan Riley McGilchrist -- Cormac McCarthy and the American Literary Tradition: Wording the End / Jan Nordby Gretlund -- Cormac McCarthy's House / Peter Josyph -- The Painterly Eye: Waterscapes in Cormac McCarthy's "The Road" / Dianne C. Luce -- The Silent Sheriff: "No Country for Old Men": A Comparison of Novel and Film / John Cant -- "A Namelessness Wheeling in the Night": Shapes of Evil in Cormac McCarthy's "Blood Meridian" and John Carpenter's "Halloween" / Michael Madsen -- "A Novel in Dramatic Form": Metaphysical Tension in "The Sunset Limited" / Ciaran Dowd -- Believing in "The Sunset Limited": Tom Cornford and Peter Josyph -- Cold Dimensions, Little Worlds: Self, Death, and Motion in "Suttree" and Beckett's "Murphy" / Euan Gallivan -- From Blue to Blood: Jean Toomer's "Blue Meridian" and Cormac McCarthy's "Blood Meridian" as Intertexts / John Ferer -- Versions of the "Seeleroman": Cormac McCarthy and Leslie Silko / Nicholas Monk; Includes bibliographical references and index
Keywords: McCarthy, Cormac, -- 1933- -- Criticism and interpretation; McCarthy, Cormac, -- 1933- -- Phê bình và diễn giải; Intertextuality; Liên văn bản